An Adolescent Female With Disordered Eating and Cannabis Use Found to Have Acute Intermittent Porphyria - Brooke Gertz; Mark Mullen; Tony Pesavento (Case Reports in Psychiatry)
Principal Conclusion: AIP is a rare but highly treatable cause of nausea, vomiting, and altered mental status in adolescents. Due to its symptomatologic overlap with more common conditions like cannabinoid hyperemesis syndrome and eating disorders, it is easily missed. Thus, a high index of suspicion is required to obtain an AIP diagnosis and initiate treatment.